Dieta del "pargo colorado" Letjanus colorado (Pisces: Lutjanidae) en el Golfo de Nicoya, Costa Rica - Rojas M., José Rodrigo (1997)
A total of 308 "Red Snapper" Lutjanus colorado were collected monthly in the Gulf of Nicoya, Costa Rica, from January 1993 to January 1994 to determine feeding habits. The fishes (16-56 cm in total length) were polychaete worms and plant debries were found in the stomach contents. The total biomass was984.2 g; 40% of the stomachs were empty. The diet has ontogenic differences: in juvenils, at any timeof the year, the most frequent and abundant components were fishes (i.e. Anchoa sp., Tomicodon sp. and Pomadasys sp.), and in adults they were panaeid shrimps (i.e. Panaeus californiensis, P. occidentalis and P. stylirostris). The maiin food of the bigger fishes (≥ 50 cm TL) were stomapods (Squilla sp.). The relative importance of different components of the diet was assessed with two indexes that combine, in different ways, porcentage frecuency of occurrence, percentage number and percentahe weigth of prey categories. The relative importance and feeding coefficient of the main dietary items did not vary during the year.